The Institution of the Maintenance of Minors in France and England and Wales in the Light of Historical Development - Krausz, Bernadett (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The paper gives an overview of the institution of the maintenance of minors in France and in England and Wales in the light of historical development, by giving a glimpse into the main reforms of French and English family law. In France, the institution is regulated in the Civil Code, in England, separate acts establish the basic concepts and principles. In both countries underage children are entitled to maintenance and the obligation does not cease, when they reach the legal age. The parents are the primary obligees. The principles of calculating the amount of maintenance are similar, the parents’ income conditions and the children’s needs and education are taken into account. The basic principles, the material law aspects are very similar between the two states, but from the procedural law point of view they have different systems.